Relation between total body load and session rating of perceived exertion in professional soccer players - Gomez-Piriz, P. T.; Jiménez-Reyes, P.; Ruiz-Ruiz, C. (The Journal of Strength and Conditioning Research, 2011)
The aims of this study were to assess (a) the validity of total body load (TBL)-obtained from the global position system (GPS) devices-to quantify soccer training load, assessing its relationship with session rating of perceived exertion (session-RPE) and (b) to analyze the differences in terms of TBL and session-RPE among defenders, midfielders, and forwards. Twenty-two professional soccer players (Spanish first division, season 2007-2008; 26.74 ± 4.2 years; height 179.74 ± 4.04 cm; weight 73.7 ± 3.35 kg) participated in the study. During 13 training sessions composed predominantly of small-sided games, TBL and RPE multiplied by the minutes of session duration were determined using GPS and the 21-point scale, respectively. In each session, data from 10 players randomly selected and classified according to player position (defenders, midfielders, and forwards) were collected. Although session-RPE was a significant predictor of TBL (? = 0.23, p < 0.05), this method only accounted for 5% of the variance in TBL. No significant differences in terms of TBL and session-RPE were found regarding player position. The results of this study suggest that TBL is not a valid measure to quantify training load because it is not strongly correlated with session-RPE. Furthermore, TBL and session-RPE in small-sided soccer games do not vary according to player positions.